Rational Misbehavior? Evaluating an Integrated Dual-Process Model of Criminal Decision Making - Gelder, Jean-Louis (Journal of quantitative criminology, 2014)
Objectives Test the hypothesis that dispositional self-control and morality relate to criminal decision making via different mental processing modes, a ‘hot’ affective mode and a ‘cool’ cognitive one. Methods Structural equation modeling in two studies under separate samples of undergraduate students using scenarios describing two different types of crime, illegal downloading and insurance fraud. Both self-control and morality are operationalized through the HEXACO model of personality (Lee and Ashton in Multivariate Behav Res 39(2):329–358, 2004 ). Results In Study 1, negative state affect, i.e., feelings of fear and worry evoked by a criminal prospect, and perceived risk of sanction were found to mediate the relations between both dispositions and criminal choice. In Study 2, processing mode was manipulated by having participants rely on either their thinking or on their feelings prior to deciding on whether or not to make a criminal choice. Activating a cognitive mode strengthened the relation between perceived risk and criminal choice, whereas activating an affective mode strengthened the relation between negative affect and criminal choice. Conclusion In conjunction, these results extend research that links stable individual dispositions to proximal states that operate in the moment of decision making. The results also add to dispositional perspectives of crime by using a structure of personality that incorporates both self-control and morality. Contributions to the proximal, state, perspectives reside in the use of a new hot/cool perspective of criminal decision making that extends rational choice frameworks.